نماذج تعلم مهارة الاستماع المنظور النظري بلتعلم السريع (accelerated learning) - Darrin, Abu; Qodir, Abdul (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2024)
The following article tries to present a theme related to maharah istima' learning, where a student can capture a lesson delivered by the teacher, and also in this theme it is related to the theory of accelerated learning, Accelerated Learning is a learning approach that pays more attention to the psychological state of students in learning. The learning concept is based on the findings of a Bulgarian psychiatrist, Dr. George Lozanov. According to Lozanov, the human brain (which is used as the main tool for learning) will only be used effectively if it is in a